A Blinding Event from Ocular Melioidosis in a Young Man in Malaysia : A Case Report - Mohd. Asyraaf, Abdul Kadir; Muhammad Adri, Mohamed Shafit; Adzura, Salam; Wan Norliza, Wan Muda (Springer Nature, 2025)
Melioidosis, caused by Burkholderia pseudomallei, is a significant public health concern in endemic regions such as Malaysia. It is often referred to as the “great mimicker” because it can afect various organs with nonspecific symptoms and signs, posing a diagnostic challenge. We report a sight-threatening case of ocular melioidosis manifesting as panophthalmitis and subretinal abscess formation, leading to irreversible blindness in a young male. The patient presented with acute right eyelid swelling, eye redness, and pain on a background of newly diagnosed diabetes mellitus and urosepsis. Ocular examination revealed right eye conjunctival injection and chemosis, hypopyon and vitritis and a diagnosis of endogenous endophthalmitis was made. Concurrent liver and left gluteal abscess raised suspicion for disseminated melioidosis. Although blood and vitreous cultures were negative, serology B. pseudomallei immunoglobulin M (IgM) was positive (titre 1:360). Despite early initiation of systemic ceftazidime and later meropenem, the eye condition deteriorated further into panophthalmitis with a subperiosteal abscess. Due to a large retinal tear extending to the optic disc, surgical intervention was deemed futile. The eye is now blind but no longer painful. The patient completed antimicrobial therapy and diabetes optimization. Given the endemicity of melioidosis in Malaysia, clinicians should maintain a high index of suspicion for ocular involvement to prevent irreversible visual morbidity.